URGENSI PENGEMBANGAN BAHAN AJAR DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Wafiqah Lubis , Fathinatul; Albina, Meyniar (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study focuses on the important and best concepts in the development of Islamic Religious Education (PAI) teaching materials. The purpose of this study is to determine the urgency of developing teaching materials in Islamic Religious Education learning. In this study, the author uses a library research method and uses data sources from literature on Islamic Religious Education and the perspectives of practitioners involved in the process of making teaching materials. To collect data, relevant sources are searched, selected, and analyzed. This is done to create a complete framework for the development of effective PAI teaching materials. The results of the study indicate that students' motivation and understanding of the subject are significantly improved through systematic and comprehensive teaching materials. Well-designed and easy-to-understand teaching materials can help students learn better. This study also emphasizes the importance of using a systematic approach that includes needs analysis, design, development, implementation, and evaluation to create teaching materials that are in accordance with the curriculum and meet students' needs. In conclusion, the development of effective PAI teaching materials not only meets students' learning needs but also improves teachers' ability to deliver lessons effectively.